ДЕРЖАВНИЙ АПАРАТ ТА ПРЕДСТАВНИКИ НОВОЇ БУРЖУАЗІЇ УКРАЇНИ В УМОВАХ ЗЛАМУ НЕПУ (КІНЕЦЬ 1927 ñ ПОЧАТОК 1930-х рр.) (Zaporizhzhia Historical Review, 2021)
The article analysis the influence of processes connected with a brake down of NEP, the development of relations between representatives of public administration of USSR and entrepreneurs at time of NEP is also exposed. Actions of the Soviet Government directed to a diffing rid of non-loyal officials in the Soviet State-Party apparat on the eve of the 1920-s ñ 1930-s.